2004
DOI: 10.1136/thx.2003.010462
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of atopic and non-atopic wheeze in 10 year old children

Abstract: Background: Wheezing occurs in both atopic and non-atopic children. The characteristics of atopic and non-atopic wheeze in children at 10 years of age were assessed and attempts made to identify whether different mechanisms underlie these states. Methods: Children were seen at birth and at 1, 2, 4 and 10 years of age in a whole population birth cohort study (n = 1456; 1373 seen at 10 years). Information was collected prospectively on inherited and early life environmental risk factors for wheezing. Skin prick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 26 publications
5
72
1
Order By: Relevance
“…However, had all children undergone allergic tests at six years, some non-allergic asthmatics could have been considered as having allergic asthma, as sensitisation to inhalant allergens increases with age. Nevertheless, not too much misclassification seems to have happened as the percentage of asthmatic children with allergic asthma (63.5%) was not lower than the one found in other studies [15,16]. Another limitation of the study is the absence of some data, which may help a more subtle interpretation: family allergy risk, smoke exposure and other risk factors.…”
Section: Limitations and Strengthsmentioning
confidence: 69%
“…However, had all children undergone allergic tests at six years, some non-allergic asthmatics could have been considered as having allergic asthma, as sensitisation to inhalant allergens increases with age. Nevertheless, not too much misclassification seems to have happened as the percentage of asthmatic children with allergic asthma (63.5%) was not lower than the one found in other studies [15,16]. Another limitation of the study is the absence of some data, which may help a more subtle interpretation: family allergy risk, smoke exposure and other risk factors.…”
Section: Limitations and Strengthsmentioning
confidence: 69%
“…The recently published data from the Isle of Wight, UK birth cohort study show that, at the age of 10 yrs, the prevalence of atopic and nonatopic wheeze were similar, but that atopic wheezing was more frequently associated with a diagnosis of asthma and treatment for asthma, whereas nonatopic wheeze was more closely associated with recurrent chest infections before the age of 2 yrs [15]. In the present study, the vast majority of wheeze and active asthma at the age of 10 yrs was nonatopic.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [15][16][17] have suggested that the role of atopy in childhood asthma has been overestimated, even in Western countries. The fact that wheeze and asthma-like symptoms are frequently associated with atopy does not imply that these two phenomena are related in the individual child.…”
Section: Discussionmentioning
confidence: 99%
“…26 A whole-population birth cohort study showed that BHR to methacholine was only detected in 65% and 23% of 10-year-old children with atopic and nonatopic wheeze, respectively. 27 Factor analysis in this study clearly demonstrated weak correlations between clinical, spirometric, and inflammatory parameters in childhood asthma. These differences can probably be explained by the fact that asthma health status has a number of distinct components.…”
Section: -12mentioning
confidence: 97%